HYDRUS-2D simulations of typical pollutant migration in a soil aquifer system in the Zibo-Weifang funnel area of China. (15th April 2022) - Yu, Hang; Li, Jianju; Liu, Jing; He, Shufei; Qin, Kena; Xia, Xinhui; Xue, Chonghua; Zhao, Qingliang; Wei, Liangliang
Abstract: To clarify the removal trends of typical pollutants in recharged water samples during soil aquifer treatment (SAT), especially the recharging performances in the funnel areas of arid regions, the Zibo-Weifang funnel area of China was selected as an example where the effects of dry-wet ratio (DWR, the ratio of the dry period to irrigation period), wet period duration (WPD, duration of one irrigation period), irrigation side length (ISL) and irrigation depth (ID) on the 50-year SAT performance were simulated using HYDRUS-2D. Experimental results revealed that the operational parameters of the DWR, WPD, ISL and ID exhibited significant effects on the bulk removal of chemical oxygen demand (COD), nitrate ( N O 3 − ), ammonium ( N H 4 + ), total phosphorus (TP) and hexavalent chromium ( C r 6 + ) . Eventually, the optimal conditions with a DWR of 3, WPD of 7 d, ISL of 100 m, and ID of 200 cm were selected for the SAT based on the simulations, and irrigation loads as high as of 84.12 m/yr were obtained. During the 50-year irrigation simulation, as much as 256 Mm 3 /yr of new water would be recharged into the Shandong Plain, which would be accompanied by the effective removal of COD, N H 4 +, TP and C r 6 + . In contrast, the N O 3 − concentrations within the obtained SAT effluent (50 m depth) were higher than those of the influent, which were closely related to the insufficient carbon sources in the deep soil and poor soil adsorption capacity. Thus, a more stringent threshold value for the nitrate reinjection concentration (e.g., 12 mg/L) was proposed. In addition, the pollutants, N O 3 −, N H 4 +, TP and C r 6 + all exhibited a penetration potential and posed potential pollution threats, especially under higher irrigation loads. Therefore, appropriate pretreatment measures should be strongly considered for the practical operation of SAT systems. Graphical abstract: Image 1 Highlights: Simulated the efficiency of SAT in different operating conditions at actual scale. N O 3 − concentration increased after SAT under different operating conditions. The concentration of N O 3 − in influent should be limited to less than 12 mg/L. Significant correlation existed in the removal of N H 4 + with COD and TP ( R 2 >0.8). The penetration risk exhibited the following trend: N O 3 − ≫ C r 6 + N H 4 + >TP.